Efektivitas Karbon Aktif dalam Pembuatan Garam Rumput Laut Cokelat (Sargassum polycystum dan Padina minor): Effectiveness of Active Carbon in the Production of Brown Seaweed Salt (Sargassum polycystum and Padina minor) - Shindy Hamidah Manteu; Nurjanah Nurjanah; Asadatun Abdullah; Tati Nurhayati; Anggrei Viona Seulalae (Jurnal Pengolahan Hasil Perikanan Indonesia, 2022)
Brown seaweed has the potential to be developed as a source of salt for hypertension, but the distinctive aroma of seaweed is still an obstacle in the final product. Activated carbon is a non-toxic material that can be used to reduce the aroma of S. polycystum and P. minor salts . The purpose of this research is to determine the concentration of activated carbon in the process of making S. polycystum and P. minor salts to produce salt that is acceptable to the public. The method used with different concentrations of activated carbon (0%, 0.50%, 0.75%, 1%, 1.25%, 1.50% (w/v)) in the salt making process ,Sensory test of aroma and characterization of seaweed salt. Salt characteristics include mineral content (Mg, Fe, Ca, Na, K), Na:K ratio, NaCl content and antioxidant activity. The optimum activated carbon concentration of S. polycystum salt is 1.50% with Mg 29.24 mg/g; Fe 0.15 mg/g; Ca 27.66 mg/g; Na:K ratio 0.87 mg/g; NaCl 33.87%; antioxidant activity 201.0 mg/L. The optimum concentration of activated carbon of P. minor salt is 1% with Mg 39.05 mg/g; Fe 0.03 mg/g; Ca 32.28 mg/g; Na:K ratio 1.97 mg/g; NaCl 28.34% and antioxidant activity 111.39 mg/L.